1989
DOI: 10.1080/00332747.1989.11024456
|View full text |Cite
|
Sign up to set email alerts
|

Cohesion, Alliance and Outcome in Group Psychotherapy

Abstract: Cohesiveness has been viewed as the group psychotherapy equivalent of the therapeutic alliance in individual treatment. Although researchers have attempted to study the concept of cohesion in group treatment, understanding of this so-called "curative" group factor remains quite primitive. In this study of 12 time-limited psychotherapy groups, with a total of 90 nonpsychotic outpatients, we explore the relationships between cohesion, alliance and treatment outcome. Our cohesion measure is a new instrument, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
143
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(152 citation statements)
references
References 15 publications
6
143
2
Order By: Relevance
“…In one study, examining members' appraisals of self-help groups (i.e., Multiple Sclerosis, Compassionate Friends, and Overeaters Anonymous groups), members who perceived that their group was well organized and had a proficient leader reported greater satisfaction with the group, higher levels of selfγesteem, and lower levels of depression (Maton, 1988). Similar findings have been obtained in other studies, which have shown that primary group outcomes are related to several features of group environments, including perceived levels of group cohesion (Budman, Soldz, Demby, Feldstein, Springer & Davis, 1989;Meredith, 1987), disruptive group dynamics (Faris & Brown, 2003), group leadership and implementation (Kulic, Horne, & Dagley, 2004), and perceived group climate (Choi, Price, & Vinokur, 2003;MacKenzie, Dies, Coché, Rutan, & Stone, 1987).…”
supporting
confidence: 77%
See 2 more Smart Citations
“…In one study, examining members' appraisals of self-help groups (i.e., Multiple Sclerosis, Compassionate Friends, and Overeaters Anonymous groups), members who perceived that their group was well organized and had a proficient leader reported greater satisfaction with the group, higher levels of selfγesteem, and lower levels of depression (Maton, 1988). Similar findings have been obtained in other studies, which have shown that primary group outcomes are related to several features of group environments, including perceived levels of group cohesion (Budman, Soldz, Demby, Feldstein, Springer & Davis, 1989;Meredith, 1987), disruptive group dynamics (Faris & Brown, 2003), group leadership and implementation (Kulic, Horne, & Dagley, 2004), and perceived group climate (Choi, Price, & Vinokur, 2003;MacKenzie, Dies, Coché, Rutan, & Stone, 1987).…”
supporting
confidence: 77%
“…As the use of group-level interventions increases in both research and applied settings, it is very important to document the possible moderators to individuals' change as a result of participating in an intervention group (Stefanek, 2004). As previous research has shown, features of group environments play an important role in determining the effectiveness of a group-level intervention (Budman et al, 1989;Choi et al, 2003;MacKenzie et al, 1987;Maton, 1988;Meredith, 1987). Thus, researchers and practitioners utilizing interventions groups may benefit from routinely asking: "How do participants' perceptions of the group environment affect their individual progress, and progress for the intervention as a whole?"…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that group-level cohesion, as rated by an independent observer of both membermember and member-leader interactions, was related to client improvement. They also noted that cohesion within the first 30 minutes of a session had the strongest relationship to outcomes (Budman et al, 1989). Other researchers have noted the importance of therapist ratings of group cohesion.…”
Section: Chapter 2 Literature Review Operationalizing Cohesionmentioning
confidence: 94%
“…conflictual) and working stages of a psychotherapy group. As such, there is strong theoretical evidence for the examination of cohesion in group psychotherapy process and outcomes (Budman et al, 1989;Kivlighan & Lilly, 1997).…”
Section: Cohesion and Consequential Outcomesmentioning
confidence: 99%